Saúde do trabalhador: acidentes de trabalho registrados no Brasil - Salla, Larissa (2022)
Worker’s health is a universal right. Brazil has one of its main aggravating factors, occupational accidents, causing damage to the injured person, to the employer and to the whole society. The objective of this work was realizing a survey of occupational accidents recorded and accounted for the Observatory of Safety and Health at Work (SmartLab) from the CATWEB data from Brazil and from the CATWEB documents of the agency of the National Institute of Social Security (INSS) of Francisco Beltrão, Paraná. Data collected via SmartLab were compiled at the level of Brazil, Brazilian regions, Brazilian states and the municipality of Francisco Beltrão, Paraná. The documents collected via INSS of Francisco Beltrão agency present the sociodemographic profile of the victims (2011 to 2019). Relative rates and frequencies used to describe the sample profile were calculated. To compare the variables, causative agent, nature of the injury and affected body parts, the following tests were performed: ANOVA, chi-square of independence and adherence, the G test with William’s correction and the MannWhitney chi-square test. Were reported via SmartLab in Brazil 5.467.417 cases of occupational accidents (2012 to 2020). In the South region, 1.221.105 accidents. In the state of Paraná, 412.002, and in the municipality of Francisco Beltrão, 3.149. The state of São Paulo had the highest frequency of notifications of occupational accidents, however, Santa Catarina, located in the Southern region, had the highest rate of accidents recorded. The most frequent causative agent in Brazil was the biological, chemical and physical agent. In the South region, in Paraná and in the municipality of Francisco Beltrão, were machines and tools. Brazil, the South region (p< 0,0001) and Paraná (p= 0,0009) showed significant differences when compared to Francisco Beltrão. As for the nature of the lesion, the most frequent variable presented a significant difference for all analyzes (p< 0,0001). For parts of the body most frequently affected, in Brazil and in the state of Paraná it was the lower limb, in the South region it was the finger and in Francisco Beltrão, the upper limb. In the INSS of the municipality of Francisco Beltrão, were reported 443 accidents. The profile showed that most accidents occur with men (80,1%), under 50 years (69,5%), single (48,7%), with income between R$500,00 to R$1.000,00 (48%) and most of them occur in urban areas (90,5%).